The occupational dimension of strategy-making: the case of the student experience 'initiative' in a UK University - Baranova, Polina (2017)
This study introduces the occupational dimension into the study of strategy-making, with particular reference to Higher Education in the UK. The concepts of occupation and self- and social identity are deployed to explore the relational dynamics amongst the occupational groupings in higher education in the context of the increasing marketisation of the sector. The personal identity work of the university employees is analysed contributing to the study of the occupational aspect of self-identities of the members of the three higher education occupational groupings: academics, manager-academics and non-academics. The concept of ‘occupational connectivity’ is introduced and developed to reveal the tensions amongst the occupational groupings and to explore the nature of these tensions in relation to the student experience initiative in a university context. University practices of strategy-making associated with the organisational approaches aimed to respond to the student experience initiative are seen as arenas where the occupational interests are acted and negotiated. A framework of four occupation strategies, representing a nexus between the levels of uncertainty and the ease of the access to economic and social opportunities, is developed. This is proposed as a useful conceptual development in the study of work and occupations due to its potential for revealing the strategies of occupational groupings in any given organisational setting.